Silicon-based negative electrode material and preparation method thereof, negative electrode, battery and electric equipment
By adopting a clad structure in the silicon-based anode material and using carbon material and fast ion conductor to cover the silicon-based core, the problems of large volume changes and low conductivity during the charge and discharge process of silicon anode material are solved, and the conductive performance of the material is improved and structural stability is enhanced.
Patent Information
- Application Number
- CN202311118699.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
The volume of the silicon negative electrode material changes greatly during repeated charging and discharge, which may lead to pulverization, and its ionic conductivity and electron conductivity are low, affecting the performance of the negative electrode.
Using a cladding structure, the silicon-based core is coated by carbon material and fast ion conductor. The mass content of the fast ion conductor gradually increases along the direction from the silicon-based core to the cladding layer to improve the conductive performance and structural stability of the material.
It improves the ionic conductivity and electronic conductivity of silicon-based anode materials, reduces volume expansion, extends the service life of the battery, and improves the cycling performance of the negative electrode and the battery.
Smart Images

Figure CN119542366A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to silicon-based negative electrode materials and preparation methods thereof, negative electrodes, batteries and electrical equipment. Background Art
[0002] Silicon negative electrode materials have attracted widespread attention due to their very high theoretical specific capacity and low lithium insertion and extraction potential. However, silicon negative electrode materials undergo large volume changes during repeated charge and discharge, and may even break up. At the same time, the ionic and electronic conductivity of silicon negative electrode materials are low, which affects the use of negative electrodes. Therefore, silicon negative electrode materials need to be improved to meet the use requirements. Summary of the invention
[0003] In view of this, the present application provides a silicon-based negative electrode material and a preparation method thereof, a negative electrode, a battery and an electrical device. The silicon-based negative electrode material has excellent ionic conductivity and electronic conductivity, which is beneficial to improving the performance of the negative electrode and the battery. At the same time, the coating layer can effectively inhibit the volume expansion of the silicon-based core, improve the service life of the negative electrode and the battery, and thus be beneficial to the use of the negative electrode and the battery.
[0004] In the first aspect, the present application provides a silicon-based negative electrode material, comprising a silicon-based core and a coating layer coating the silicon-based core, wherein the coating layer is made of a carbon material and a fast ion conductor, and the mass content of the fast ion conductor in the coating layer gradually increases along the direction from the silicon-based core to the coating layer.
[0005] Optionally, along the direction from the silicon-based core to the coating layer, the mass content of the fast ion conductor in the coating layer gradually increases from 15%-25% to 60%-70%.
[0006] Optionally, the coating layer has a thickness of 5nm-50nm, and the particle size of the silicon-based core is 25nm-50nm.
[0007] Optionally, the mass content of the silicon-based core in the silicon-based negative electrode material is 50%-70%, and the mass content of the coating layer is 30%-50%.
[0008] Optionally, the fast ion conductor includes at least one of zirconium oxide, aluminum oxide, thorium dioxide, hafnium dioxide, germanium dioxide, bismuth oxide, lanthanum aluminate, calcium titanate, strontium titanate, calcium fluoride, lead difluoride, stannous chloride and silver iodide.
[0009] Optionally, the silicon-based negative electrode material further includes a carbon layer, wherein the carbon layer covers the coating layer, and the thickness of the carbon layer is 2nm-10nm.
[0010] In the second aspect, the present application provides a method for preparing a silicon-based negative electrode material, comprising: forming a coating layer covering the silicon-based core on the surface of the silicon-based core to obtain a silicon-based negative electrode material, wherein the material of the coating layer comprises a carbon material and a fast ion conductor, and along the direction from the silicon-based core to the coating layer, the mass content of the fast ion conductor in the coating layer gradually increases.
[0011] Optionally, a silicon source is mixed with a fast ion conductor source and a carbon source and then sintered to obtain the silicon-based negative electrode material, wherein the silicon source forms the silicon-based core, the fast ion conductor source forms the fast ion conductor, and the carbon source forms the carbon material.
[0012] In a third aspect, the present application provides a negative electrode, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises the silicon-based negative electrode material described in the first aspect, or the silicon-based negative electrode material prepared by the preparation method described in the second aspect.
[0013] In a fourth aspect, the present application provides a battery, comprising a positive electrode and the negative electrode described in the third aspect.
[0014] In a fifth aspect, the present application provides an electrical device, comprising the battery described in the fourth aspect.
[0015] The present application provides that the setting of the coating layer in the silicon-based negative electrode material improves the ionic conductivity and electronic conductivity of the silicon-based negative electrode material, and the gradual distribution of the mass content of the fast ion conductor makes it easy to deintercalate active ions at the contact interface between the silicon-based negative electrode material and the electrolyte, which is beneficial to reducing the negative electrode interface impedance and reducing the internal resistance of the battery. At the same time, it can also improve the initial efficiency of the silicon-based material. At the same time, the coating layer covers the silicon-based core, which can effectively inhibit the volume expansion of the silicon-based core and avoid the occurrence of undesirable phenomena such as cracking and crushing of the silicon-based negative electrode material, which is beneficial to improving the negative electrode and battery cycle performance; the preparation method of the silicon-based negative electrode material is simple and easy to operate, and can realize large-scale preparation of silicon-based negative electrode materials, which is beneficial to the use of silicon-based negative electrode materials; the negative electrode and battery with the silicon-based negative electrode material have excellent performance, which is beneficial to its use in electrical equipment and improves the product competitiveness of electrical equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0017] Figure 1 A schematic cross-sectional view of a silicon-based negative electrode material provided in one embodiment of the present application.
[0018] Figure 2 A schematic cross-sectional view of a silicon-based negative electrode material provided in another embodiment of the present application.
[0019] Figure 3 A schematic cross-sectional view of a negative electrode provided in one embodiment of the present application.
[0020] Figure 4 This is an electron microscope image of the silicon-based negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0022] See also Figure 1 , is a cross-sectional schematic diagram of a silicon-based negative electrode material provided in one embodiment of the present application, wherein the silicon-based negative electrode material 100 comprises a silicon-based core 10 and a coating layer 20 coating the silicon-based core 10, wherein the coating layer 20 is made of a carbon material and a fast ion conductor, and the mass content of the fast ion conductor in the coating layer 20 gradually increases along the direction from the silicon-based core 10 to the coating layer 20. In the present application, the coating layer coated on the surface of the silicon-based core can inhibit the increase in the volume of the silicon-based core during the charge and discharge process, thereby reducing the volume expansion of the silicon-based negative electrode material and improving the structural stability of the silicon-based negative electrode material; the carbon material in the coating layer can improve the electronic conductivity of the silicon-based negative electrode material, and the fast ion conductor in the coating layer can improve the ionic conductivity of the silicon-based negative electrode material. At the same time, the mass content of the fast ion conductor gradually increases along the direction from the silicon-based core to the coating layer, making it easier for active ions to be embedded and released on the surface of the silicon-based negative electrode material, thereby helping to improve the electrochemical performance of the negative electrode and the battery.
[0023] In the present application, the silicon-based core has a higher specific capacity, which ensures the performance of the silicon-based negative electrode material. In one embodiment of the present application, the material of the silicon-based core includes at least one of elemental silicon, silicon-oxygen material, silicon-carbon material and silicon alloy material. It can be understood that the silicon-oxygen material is a material containing silicon and oxygen elements, the silicon-carbon material is a material containing silicon and carbon elements, and the silicon alloy material is a material containing silicon and metal elements. Specifically, the silicon alloy material can be, but is not limited to, at least one of ferrosilicon alloy, silicon-copper alloy, silicon-aluminum alloy and silicon-lithium alloy.
[0024] In the present application, the shape of the silicon-based core is not limited, and specifically can be but not limited to spherical, quasi-spherical, etc. In one embodiment of the present application, the particle size of the silicon-based core is 25nm-50nm, which is not only conducive to increasing the silicon content in the silicon-based negative electrode material, but also to increasing its specific capacity. At the same time, it can reduce the volume change of the silicon-based core during charging and discharging, better inhibit the volume expansion of the silicon-based core, and can also shorten the diffusion path of ions and electrons, and improve the performance of the silicon-based negative electrode material. The particle size in the present application is the volume median diameter D50, and the particle size can be measured by a laser particle size distribution instrument. Specifically, the particle size of the silicon-based core can be but not limited to 25nm, 28nm, 30nm, 34nm, 35nm, 39nm, 40nm, 45nm, 48nm or 50nm, etc. In one embodiment of the present application, the particle size of the silicon-based core can be 30nm-45nm, which helps to further improve the structural stability and performance of the silicon-based negative electrode material. In another embodiment of the present application, the particle size of the silicon-based core can be 20nm-40nm. In another embodiment of the present application, the particle size of the silicon-based core may be 35nm-50nm.
[0025] In one embodiment of the present application, the mass content of the silicon-based core in the silicon-based negative electrode material is 50%-70%, which is conducive to increasing the silicon content in the silicon-based negative electrode material and improving its specific capacity. Specifically, the mass content of the silicon-based core in the silicon-based negative electrode material can be but is not limited to 50%, 52%, 55%, 57%, 60%, 63%, 65%, 68% or 70%, etc. In one embodiment of the present application, the mass content of the silicon-based core in the silicon-based negative electrode material can be 50%-60%. In another embodiment of the present application, the mass content of the silicon-based core in the silicon-based negative electrode material can be 60%-70%.
[0026] In one embodiment of the present application, the silicon-based core is a porous structure, which is conducive to alleviating the volume expansion of the silicon-based core during the charge and discharge process and improving the structural stability of the silicon-based negative electrode material. That is to say, the silicon-based core has a pore structure, and the pore structure can be a through hole or a blind hole. In one embodiment of the present application, the porosity of the silicon-based core is 5%-30%, which helps to buffer the volume expansion of the silicon-based core during the charge and discharge process, while ensuring the strength of the silicon-based core and improving the structural stability of the silicon-based core. The porosity in this application is obtained by BET method detection. Specifically, the porosity of the silicon-based core can be but not limited to 5%, 10%, 15%, 20%, 25% or 30%, etc. In one embodiment, the porosity of the silicon-based core can be 5%-15%. In another embodiment, the porosity of the silicon-based core can be 10%-20%.
[0027] The coating layer of the present application can inhibit the volume expansion of the silicon-based core, and the carbon material and fast ion conductor in the coating layer can improve the electronic and ionic conductivity of the silicon-based negative electrode material, thereby improving the electrochemical performance of the silicon-based negative electrode material. Fast ion conductors are also called superionic conductors, which have ionic conductivity comparable to that of liquid electrolytes within a certain temperature range (10 -6 S cm -1 ) and low ion conductivity activation energy (≤0.40eV). In the present application, the fast ion conductor may be at least one of oxides, oxyacid salts, fluorides, chlorides and iodides. In one embodiment of the present application, the fast ion conductor includes at least one of zirconium oxide, aluminum oxide, thorium dioxide, hafnium dioxide, germanium dioxide, bismuth oxide, lanthanum aluminate, calcium titanate, strontium titanate, calcium fluoride, lead difluoride, stannous chloride and silver iodide. The above-mentioned fast ion conductor is conducive to improving the ionic conductivity of silicon-based negative electrode materials. In one embodiment of the present application, the fast ion conductor is an alkaline substance, which is conducive to reducing the surface moisture of silicon-based negative electrode materials during the preparation of silicon-based negative electrode materials, and further improving the performance of silicon-based negative electrode materials. Specifically, the fast ion conductor may include at least one of aluminum oxide, germanium dioxide and calcium titanate. In one embodiment of the present application, the carbon material includes at least one of graphite, carbon black, graphene, carbon nanotubes, carbon nanofibers and amorphous carbon (such as hard carbon, soft carbon, etc.). The use of the above-mentioned carbon materials is beneficial to improving the conductivity of silicon-based negative electrode materials.
[0028] In one embodiment of the present application, the thickness of the coating layer is 5nm-50nm, which can not only coat the silicon-based core, but also improve the electronic conductivity and ionic conductivity of the silicon-based negative electrode material. Specifically, the thickness of the coating layer can be, but is not limited to, 5nm, 8nm, 10nm, 15nm, 17nm, 20nm, 28nm, 30nm, 34nm, 40nm, 46nm or 50nm. In one embodiment of the present application, the thickness of the coating layer can be 5nm-15nm. In another embodiment of the present application, the thickness of the coating layer can be 20nm-45nm.
[0029] In one embodiment of the present application, the mass content of the coating layer in the silicon-based negative electrode material is 30%-50%, which is beneficial to improve the electronic and ionic conductivity and structural stability of the silicon-based negative electrode material. Specifically, the mass content of the coating layer in the silicon-based negative electrode material may be, but is not limited to, 30%, 33%, 35%, 37%, 40%, 42%, 45%, 47% or 50%, etc. In one embodiment of the present application, the mass content of the coating layer in the silicon-based negative electrode material may be 30%-40%. In another embodiment of the present application, the mass content of the coating layer in the silicon-based negative electrode material may be 40%-50%.
[0030] In one embodiment of the present application, the coverage of the coating layer is greater than or equal to 70%. The coverage of the coating layer is the ratio of the surface area of the silicon-based core coated by the coating layer to the surface area of the silicon-based core. Specifically, the coverage of the coating layer can be, but is not limited to, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 95% or more, or 100%.
[0031] In the present application, the mass content of the fast ion conductor gradually increases along the direction from the silicon-based core to the coating layer, that is, the content of the fast ion conductor in the area close to the surface of the silicon-based negative electrode material is high, which is conducive to the rapid embedding and extraction of active ions (such as lithium ions, sodium ions, etc.), which can not only reduce the negative electrode interface impedance, reduce the internal resistance of the battery, and increase the high-rate fast charging performance, but also avoid the problems such as short circuit caused by the precipitation of active ions on the negative electrode surface, improve the safety of the negative electrode, and thus help to improve the electrochemical performance of the negative electrode and the battery. The "gradual increase" in the present application can be a linear increase or a nonlinear increase, etc. The nonlinear increase can be a parabolic increase, a parabolic increase, a gradient increase, etc. In one embodiment of the present application, the gradual increase can be to remain unchanged first, and then increase in a parabolic shape. In another embodiment of the present application, the gradual increase can be a linear increase. In another embodiment of the present application, the gradual increase can be to remain unchanged first, and then increase in a gradient. In one embodiment of the present application, along the direction from the silicon-based core to the coating layer, the mass content of the fast ion conductor in the coating layer gradually increases from 15%-25% to 60%-70%, which is beneficial to further improve the capacity and cycle performance of the battery and increase the service life of the battery. Specifically, the mass content of the fast ion conductor in the coating layer can be gradually increased from 15%-20%, 18%-25%, 20%-23% or 20%-25% to 60%-65%, 63%-66%, 64%-69% or 65%-70%, etc.
[0032] See also Figure 2 , is a cross-sectional schematic diagram of a silicon-based negative electrode material provided in another embodiment of the present application, which is Figure 1 The difference is that the silicon-based negative electrode material 100 further includes a carbon layer 30, and the carbon layer 30 covers the coating layer 20. The carbon layer can further improve the conductivity of the silicon-based negative electrode material, and at the same time help to reduce the expansion of the silicon-based negative electrode material, improve the performance of the silicon-based negative electrode material in deintercalating active ions, and further help to improve the cycle performance of the negative electrode.
[0033] In one embodiment of the present application, the thickness of the carbon layer is 2nm-10nm, which can not only improve the performance of the silicon-based negative electrode material, but also avoid the adhesion between the silicon-based negative electrode materials, which is conducive to the use of silicon-based negative electrode materials. Specifically, the thickness of the carbon layer can be but is not limited to 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm or 9nm, etc. In one embodiment of the present application, the material of the carbon layer includes at least one of graphite, carbon black, graphene, carbon nanotubes, carbon nanofibers and amorphous carbon (such as hard carbon, soft carbon, etc.). In the present application, the material of the carbon material in the coating layer and the carbon layer can be the same or different, and can be selected according to needs. In one embodiment of the present application, the carbon material in the coating layer includes graphite, and the material of the carbon layer includes hard carbon, so that the coating layer and the carbon layer can better cooperate, improve the performance of the silicon-based negative electrode material, thereby improving the electrochemical performance of the battery. In one embodiment of the present application, when the silicon-based negative electrode material has a carbon layer, the mass and proportion of the carbon material and the carbon layer in the coating layer of the silicon-based negative electrode material is 20%-30%, thereby ensuring the conductive performance of the silicon-based negative electrode material. Specifically, the mass and proportion of the carbon material and the carbon layer in the coating layer of the silicon-based negative electrode material may be, but not limited to, 20%, 22%, 25%, 27%, 28% or 30%, etc. In one embodiment of the present application, the coverage of the carbon layer is greater than or equal to 70%. Among them, the coverage of the carbon layer is the ratio of the surface area of the coating layer coated by the carbon layer to the surface area of the coating layer. Specifically, the coverage of the carbon layer may be, but not limited to, more than 70%, more than 75%, more than 80%, more than 85%, more than 90%, more than 95% or 100%, etc.
[0034] The present application provides a method for preparing a silicon-based negative electrode material, comprising: forming a coating layer covering a silicon-based core on the surface of a silicon-based core to obtain a silicon-based negative electrode material, wherein the material of the coating layer comprises a carbon material and a fast ion conductor, and the mass content of the fast ion conductor in the coating layer gradually increases along the direction from the silicon-based core to the coating layer. The method for preparing a silicon-based negative electrode material provided in the present application can produce the silicon-based negative electrode material in any of the above-mentioned embodiments. In the present application, a coating layer can be formed on the surface of a silicon-based core by at least one of a ball milling method, a liquid phase method (such as a coprecipitation method, a hydrothermal method, a sol-gel method, etc.) and a gas phase method.
[0035] In one embodiment of the present application, after the silicon source is mixed with the fast ion conductor source and the carbon source, a silicon-based negative electrode material is obtained by sintering, wherein the silicon source forms a silicon-based core, the fast ion conductor source forms a fast ion conductor, and the carbon source forms a carbon material. The fast ion source and the carbon source are coated on the surface of the silicon source by mixing. In one embodiment of the present application, after the silicon source and the carbon source are mixed, the fast ion conductor source is added in batches, and a silicon-based negative electrode material is obtained by sintering, wherein the silicon source forms a silicon-based core, the fast ion conductor source forms a fast ion conductor, and the carbon source forms a carbon material. The fast ion source and the carbon source are coated on the surface of the silicon source by mixing. Due to the existence of the Kirkendall effect, by adding the fast ion conductor source in batches and gradually reducing the amount of the fast ion conductor source added, a silicon-based negative electrode material with a gradually changing mass content of the fast ion conductor can be obtained after sintering.
[0036] In one embodiment of the present application, the silicon source includes at least one of an inorganic silicon source and an organic silicon source. Specifically, the inorganic silicon source can be selected according to the material of the required silicon core, such as elemental silicon particles, silicon oxygen particles (such as silicon dioxide particles, etc.), silicon carbon particles, silicon alloy particles, etc.; the organic silicon source can include but is not limited to diphenylsilane, tetrabutyl orthosilicate, tetraethyl orthosilicate, 3-aminopropyl triethoxysilane, methyl trimethoxysilane, methyl triethoxysilane, dimethyl diethoxysilane, ethyl trimethoxysilane and ethyl triethoxysilane. In one embodiment, the particle size of the inorganic silicon source can be 25nm-50nm. Specifically, the particle size of the inorganic silicon source can be but is not limited to 25nm, 28nm, 30nm, 33nm, 35nm, 39nm, 40nm, 43nm, 45nm, 47nm or 50nm, etc. In one embodiment of the present application, the fast ion conductor source includes at least one of a fast ion conductor and a fast ion conductor precursor. Specifically, the material of the fast ion conductor precursor can be selected according to the specific material of the fast ion conductor in the coating layer. For example, the fast ion conductor precursor can be zirconium tetrachloride, and the obtained fast ion conductor is zirconium oxide; for another example, the fast ion conductor precursor can be aluminum chloride, and the obtained fast ion conductor is aluminum oxide. In one embodiment of the present application, the carbon source includes at least one of a carbon material and a carbon precursor. Specifically, the carbon material can include but is not limited to at least one of graphite, carbon black, graphene, carbon nanotubes, carbon nanofibers and amorphous carbon; the carbon precursor can include but is not limited to at least one of glucose, starch, sucrose, asphalt, petroleum coke and paraffin.
[0037] In one embodiment of the present application, a silicon source is mixed with a fast ion conductor source and a carbon source and then added to a solvent, and then dried and sintered to obtain a silicon-based negative electrode material. In the present application, the solvent is used to disperse the silicon source, the fast ion conductor source and the carbon source, and the solvent can volatilize during the drying and sintering process without affecting the silicon-based negative electrode material. In one embodiment, the solvent may include at least one of water, ethanol, n-hexane, n-pentane, n-heptane, cyclohexane and cyclopentane. In a specific embodiment, the solvent may include water and ethanol, and the molar ratio of water to ethanol may be (0.25-4): 1. Specifically, the molar ratio of water to ethanol may be, but is not limited to, 0.25:1, 0.5:1, 0.7:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1, etc.
[0038] In one embodiment of the present application, a silicon source, a fast ion conductor source, a carbon source and a surfactant can be added to a solvent to form a mixed solution, and the mixed solution is dried and sintered to obtain a silicon-based negative electrode material. Adding a surfactant can improve the dispersion performance of each component, which is beneficial to the formation and coating of the coating layer. Specifically, the surfactant can include but is not limited to at least one of sodium dodecyl sulfate, stearic acid, lauryl glucoside, monostearate glycerol and polysorbate. In one embodiment, the mass content of the surfactant in the mixed solution is 0.5%-5%, which is beneficial to the dispersion of each component and the formation of the coating layer. Specifically, the mass content of the surfactant in the mixed solution can be but is not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc. In one embodiment, an inorganic silicon source, a fast ion conductor precursor, a carbon precursor, a surfactant and a solvent can be mixed and sintered to obtain a silicon-based negative electrode material.
[0039] In one embodiment of the present application, sintering includes processing at 800°C-900°C for 3h-5h, which is conducive to the formation of the coating layer. Specifically, the sintering temperature may be, but not limited to, 800°C, 825°C, 840°C, 850°C, 875°C, 880°C or 900°C, and the sintering time may be, but not limited to, 3h, 3.5h, 4h, 4.5h or 5h, etc.; sintering is followed by cooling and annealing. In one embodiment, sintering is performed in a vacuum environment or a protective atmosphere, and the protective atmosphere may include, but is not limited to, at least one of nitrogen, argon, and hydrogen. In one embodiment, sintering is performed in a protective atmosphere, and the protective atmosphere includes 5%-10% hydrogen by volume and 90%-95% argon by volume. In one embodiment, sintering also includes heating to 800°C-900°C at a heating rate of 3°C / min-5°C / min. Specifically, the heating rate may be, but is not limited to, 3°C / min, 3.2°C / min, 3.5°C / min, 3.8°C / min, 4°C / min, 4.5°C / min, 4.7°C / min or 5°C / min, etc. In one embodiment of the present application, drying includes treating at 100°C-200°C for 12h-30h, which is conducive to the removal of the solvent. Specifically, the drying temperature may be, but is not limited to, 100°C, 125°C, 150°C, 175°C, 180°C or 200°C, etc., and the drying time may be, but is not limited to, 12h, 15h, 18h, 20h, 25h, 27h or 30h, etc.
[0040] In one embodiment of the present application, a fast ion source and a carbon source are used to form a coating layer on the surface of a silicon source by vapor deposition to obtain a silicon-based negative electrode material. Specifically, vapor deposition can be, but is not limited to, physical vapor deposition (such as magnetron sputtering, vacuum evaporation, ion plating, etc.), chemical vapor deposition (such as thermal chemical vapor deposition, plasma chemical vapor deposition, etc.), atomic layer deposition, etc. In the present application, by controlling the proportion of the carbon source, the power of the carbon source, the proportion of the fast ion conductor source, the power of the fast ion conductor source, the deposition speed, the deposition temperature, the deposition time, etc. during the deposition process, the gradual distribution of the fast ion conductor in the coating layer is achieved. In one embodiment, silicon particles are placed in a deposition chamber, a zirconium oxide target is set, and ethylene gas is introduced. During the deposition process, the target current and / or target power of the zirconium oxide target is changed, and the amount of ethylene gas introduced remains unchanged. After deposition, a silicon-based negative electrode material is obtained. The silicon-based negative electrode material includes a silicon element and a coating layer. The coating layer includes zirconium oxide and a carbon material. Along the direction from the silicon element to the coating layer, the mass content of zirconium oxide in the coating layer gradually increases.
[0041] In one embodiment of the present application, a method for preparing a silicon-based negative electrode material includes: forming a coating layer covering a silicon-based core on a surface of a silicon-based core, and forming a carbon layer covering the coating layer on a surface of the coating layer to obtain a silicon-based negative electrode material. Specifically, the carbon layer can be formed by at least one of a ball milling method, a liquid phase method, and a gas phase method.
[0042] The preparation method of the silicon-based negative electrode material provided in the present application is simple and easy to control, and can obtain a silicon-based negative electrode material with excellent electronic conductivity, ionic conductivity and small volume expansion effect.
[0043] The present application provides a negative electrode, including a negative electrode active material layer, wherein the negative electrode active material layer includes the silicon-based negative electrode material in any of the above embodiments, or the silicon-based negative electrode material obtained in any of the above embodiments. The negative electrode having the silicon-based negative electrode material has high initial efficiency, excellent rate performance and cycle performance, which is conducive to its use in batteries.
[0044] In one embodiment of the present application, the mass content of the silicon-based negative electrode material in the negative electrode active material layer is greater than or equal to 80%, which is beneficial to improving the electrochemical performance of the negative electrode. Specifically, the mass content of the silicon-based negative electrode material in the negative electrode active material layer is greater than or equal to 82%, 85%, 88%, 90%, 93%, 95%, 97% or 98%, etc.
[0045] In one embodiment of the present application, the negative electrode active material layer may also include at least one of a negative electrode conductor and a negative electrode binder. Specifically, the negative electrode conductor may include but is not limited to at least one of conductive carbon black, carbon nanotubes, carbon fibers, carbon black and graphite; the negative electrode binder may include but is not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene latex, and nitrile rubber. In one embodiment of the present application, the mass content of the negative electrode conductor in the negative electrode active material layer is less than or equal to 5%. Specifically, the mass content of the negative electrode conductor in the negative electrode active material layer may be but is not limited to 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%, etc. In one embodiment, the mass content of the negative electrode conductor in the negative electrode active material layer may be 0.1%-5%. In one embodiment of the present application, the mass content of the negative electrode binder in the negative electrode active material layer is less than or equal to 10%. Specifically, the mass content of the negative electrode binder in the negative electrode active material layer may be, but is not limited to, 0.1%, 0.5%, 2%, 4%, 5%, 7%, 8% or 9%, etc. In one embodiment, the mass content of the negative electrode binder in the negative electrode active material layer is 0.1%-10%.
[0046] In one embodiment of the present application, the thickness of the negative electrode active material layer is 10 μm-100 μm, which can ensure the electrochemical performance of the negative electrode without increasing the weight of the negative electrode too much. Specifically, the thickness of the negative electrode active material layer can be, but is not limited to, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, etc.
[0047] In one embodiment of the present application, the negative electrode further comprises a negative electrode current collector, and the negative electrode active material layer is disposed on the surface of the negative electrode current collector. Figure 3 , is a cross-sectional schematic diagram of a negative electrode provided in one embodiment of the present application, wherein the negative electrode 200 includes a negative electrode current collector 210 and a negative electrode active material layer 220 disposed on the surface of the negative electrode current collector 210, and the negative electrode active material layer 220 includes a silicon-based negative electrode material. In one embodiment of the present application, the negative electrode current collector is selected from a metal foil or an alloy foil. Among them, the metal foil includes copper, aluminum, nickel, iron or cobalt foil, and the alloy foil includes an alloy of at least one element of copper, aluminum, nickel, iron and cobalt or stainless steel. In one embodiment, the material of the negative electrode current collector includes at least one of copper, aluminum, nickel, iron and cobalt or stainless steel. Specifically, the negative electrode current collector can be copper foil. In one embodiment of the present application, at least one of a binder and a conductive agent can be mixed with a silicon-based negative electrode material in an organic solvent to form a mixed slurry, and the mixed slurry is coated on the surface of the negative electrode current collector, and the negative electrode is obtained after drying.
[0048] The present application provides a battery, comprising a positive electrode and a negative electrode in any of the above embodiments. The battery having the negative electrode has excellent first efficiency, rate performance and cycle performance, which is beneficial to the use of the battery. Specifically, the battery can be, but is not limited to, a lithium ion battery, a sodium ion battery, etc.
[0049] In one embodiment of the present application, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector. In one embodiment of the present application, the positive electrode current collector is selected from a metal foil or an alloy foil. Among them, the metal foil includes copper, titanium, aluminum, platinum, iridium, ruthenium, nickel, tungsten, tantalum, gold or silver foil, and the alloy foil includes stainless steel, or an alloy containing at least one element of copper, titanium, aluminum, platinum, iridium, ruthenium, nickel, tungsten, tantalum, gold and silver. Specifically, the positive electrode current collector can be aluminum foil.
[0050] In one embodiment of the present application, the positive electrode active material layer includes at least one of a positive electrode binder and a positive electrode conductor, and a positive electrode active material. Specifically, the positive electrode active material includes at least one of a layered structure oxide (such as lithium cobalt oxide, nickel cobalt manganese oxide ternary, nickel cobalt aluminum oxide ternary, transition metal layered oxide, etc.), a polyanion material (such as lithium iron phosphate, lithium iron manganese phosphate, sodium iron phosphate, sodium vanadium phosphate, etc.), and a spinel oxide (such as lithium manganese oxide, lithium nickel manganese oxide, etc.); the positive electrode conductor may include but is not limited to at least one of conductive carbon black, carbon nanotubes, carbon fiber, carbon black and graphite; the positive electrode binder may include but is not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene butadiene latex and nitrile rubber. In one embodiment, the mass content of the positive electrode active material in the positive electrode active material layer is greater than or equal to 80%, which is conducive to improving the electrochemical performance of the positive electrode. Specifically, the mass content of the positive electrode active material in the positive electrode active material layer is greater than or equal to 82%, 85%, 88%, 90%, 93%, 95%, 97% or 98%, etc. In one embodiment, the mass content of the positive electrode conductive agent in the positive electrode active material layer is less than or equal to 5%. Specifically, the mass content of the positive electrode conductive agent in the positive electrode active material layer may be, but not limited to, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%, etc. In one embodiment, the mass content of the positive electrode conductive agent in the positive electrode active material layer may be 0.1%-5%. In one embodiment, the mass content of the positive electrode binder in the positive electrode active material layer is less than or equal to 10%. Specifically, the mass content of the positive electrode binder in the positive electrode active material layer may be, but not limited to, 0.1%, 0.5%, 2%, 4%, 5%, 7%, 8% or 9%, etc. In one embodiment, the mass content of the positive electrode binder in the positive electrode active material layer is 0.1%-10%.
[0051] In one embodiment of the present application, the battery further comprises an electrolyte. In one embodiment of the present application, at least part of the positive electrode is immersed in the electrolyte, and at least part of the negative electrode is immersed in the electrolyte, so as to ensure the normal operation of the battery. In one embodiment of the present application, the electrolyte comprises a solute and an organic solvent. Among them, the solute can be selected according to the type of battery, for example, the solute of the electrolyte in a lithium-ion battery can be a lithium salt, and the solute of the electrolyte in a sodium-ion battery can be a sodium salt. Specifically, the lithium salt may include but is not limited to at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium hexafluoroborate and lithium bis(trifluoromethanesulfonyl imide); the sodium salt may include but is not limited to at least one of sodium hexafluorophosphate, sodium bis(fluorosulfonyl imide), sodium bis(trifluoromethylsulfonyl imide), sodium tetrafluoroborate, sodium difluorooxalatoborate and sodium perchlorate; the organic solvent may include but is not limited to at least one of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0052] The present application provides an electrical device, including a battery in any of the above embodiments. The battery in the electrical device provided in the present application has excellent electrochemical properties, thereby improving the performance and service life of the electrical device. Specifically, the electrical device may refer to a vehicle, an electronic device, an energy storage system, etc., and the above battery may be provided in the electrical device in the form of a single cell, a battery module, a battery pack, etc.
[0053] The effect of the technical solution of this application is further illustrated below through specific examples.
[0054] Example 1
[0055] In a reactor containing a solvent with a molar ratio of water to ethanol of 1:1, 3g of zirconium tetrachloride (added three times, the mass ratio of the first, second and third additions is 1:2:3, the second addition time corresponds to 1 / 3 of the total reaction time, and the third addition time corresponds to 2 / 3 of the total reaction time), 2g of glucose and 0.2g of sodium dodecylbenzene sulfonate were added. After ultrasonication for 1h, 5g of silicon powder was added, and ultrasonication was repeated for 15min before transferring to a 180℃ oven for reaction for 24h. After natural cooling, centrifugation, washing with deionized water and ethanol several times and cleaning. The obtained product was placed in a tubular furnace and a gas source (5% H 2 Add 95% Ar), the heating rate is 5℃ / min, heated to 900℃ and kept warm for 3.5h, and then annealed to obtain a silicon-based negative electrode material. The silicon-based negative electrode material includes silicon and a coating layer. The coating layer includes zirconium oxide and carbon material. From the direction from the silicon to the coating layer, the mass content of zirconium oxide in the coating layer gradually increases. The above-prepared silicon-based negative electrode material was tested using a scanning electron microscope, and the results are as follows Figure 4 As shown, it can be seen that the prepared silicon-based negative electrode material has an irregular morphology and a relatively smooth surface.
[0056] Example 2
[0057] The difference from Example 1 is that the mass of zirconium tetrachloride added is 1 g.
[0058] Example 3
[0059] The difference from Example 1 is that the mass of glucose added is 0.5 g.
[0060] Example 4
[0061] The difference from Example 1 is that the particle size of the added silicon powder is 60 nm.
[0062] Example 5
[0063] The difference from Example 1 is that the particle size of the added silicon powder is 10 nm.
[0064] Example 6
[0065] The difference from Example 1 is that calcium titanate is used as the fast ion conductor source, and the coating layer includes calcium titanate and carbon material.
[0066] Example 7
[0067] It is substantially the same as Example 1, except that after the coating layer is prepared, it is coated with asphalt, and a carbon layer is prepared on the surface of the coating layer to obtain a silicon-based negative electrode material.
[0068] Comparative Example 1
[0069] The method is substantially the same as Example 1, except that zirconium tetrachloride is not added, and the prepared silicon-based negative electrode material includes a silicon-based core and a carbon layer covering the silicon-based core.
[0070] Comparative Example 2
[0071] It is substantially the same as Example 1, except that glucose is not added, and the prepared silicon-based negative electrode material includes a silicon-based core and a zirconium oxide layer coating the silicon-based core.
[0072] Comparative Example 3
[0073] Commercial silicon-carbon materials are directly used as silicon-based negative electrode materials.
[0074] Comparative Example 4
[0075] It is roughly the same as Example 1, except that 3g of zirconium tetrachloride is directly added at one time. The prepared silicon-based negative electrode material includes a silicon-based core and a coating layer coating the silicon-based core. The material of the coating layer includes carbon material and zirconium oxide, and the carbon material and zirconium oxide are evenly distributed in the coating layer.
[0076] Comparative Example 5
[0077] It is roughly the same as Example 1, except that 3g of zirconium tetrachloride is added (added in three times, the mass ratio of the first, second and third additions is 3:2:1, the time of the second addition corresponds to 1 / 3 of the total reaction time, and the time of the third addition corresponds to 2 / 3 of the total reaction time). The prepared silicon-based negative electrode material includes a silicon-based core and a coating layer coating the silicon-based core, the material of the coating layer includes carbon material and zirconium oxide, and the mass content of zirconium oxide in the coating layer gradually decreases along the direction from the silicon-based core to the coating layer.
[0078] Performance Testing
[0079] The particle size of the silicon powder in the embodiments and comparative examples was detected by the laser particle size analyzer method / instrument; the thickness of the coating layer in the silicon-based negative electrode material obtained in the embodiments and comparative examples was detected by the TEM method / instrument; the content distribution of zirconium or calcium in the coating layer close to the silicon-based core to the coating layer in the cross-section of the silicon-based negative electrode material was tested by EDS, and the content of the inner layer fast ion conductor (zirconium oxide or calcium titanate) was deduced; the content distribution of zirconium or calcium on the surface of the coating layer far away from the silicon-based core in the coating layer of the cross-section of the silicon-based negative electrode material was tested by EDS, and the content of the outer layer fast ion conductor (zirconium oxide or calcium titanate) was deduced. The results are shown in Table 1.
[0080] Table 1 Performance test results of silicon-based negative electrode materials
[0081]
[0082] The silicon-based negative electrode materials prepared in the examples and comparative examples were mixed with acetylene black and sodium carboxymethyl cellulose at a mass ratio of 8:1:1 and then coated on copper foil to obtain a negative electrode. A metal lithium sheet was used as a counter electrode, a PE / PP composite diaphragm (polyethylene / polypropylene) was used as an ion exchange membrane, and an electrolyte (including 12.93 parts by mass of LiPF 6 , 26.95 parts of EC, 30.89 parts of EMC, 11.62 parts of DMC, 10.60 parts of DEC, 5 parts of FEC, and 2 parts of VC) were used to make button batteries, and the performance of the button batteries was tested using the Blue Electric Battery Test System.
[0083] The button cell was discharged at 0.5C constant current to 0.005V at 25°C, and then charged to 1.5V at 0.5C constant current. The discharge capacity and charge capacity of the button cell were recorded and the charge and discharge efficiency (coulomb efficiency) was calculated, where the charge and discharge efficiency (%) = 100% × charge capacity / discharge capacity, and the first coulomb efficiency was obtained. Before assembling the button cell, the initial thickness of each negative electrode was measured with a micrometer. 0 After making a button cell and cycling it for 100 cycles, the battery was discharged to 0 SOC. The button cell was disassembled and the negative electrode was taken out. The negative electrode was cleaned with diethylmethylammonium chloride solution and dried. The thickness of the negative electrode after cycling was measured. 1 , calculate the expansion rate, where expansion rate (%) = 100% × (h 1 -h 0 ) / h 0 The test results are shown in Table 2.
[0084] Table 2 Performance test results of button batteries
[0085]
[0086]
[0087] It can be seen that compared with the embodiment, the battery provided in the comparative example has more irreversible lithium loss, poor cycle performance, and large expansion; the battery provided in the embodiment has less irreversible lithium loss, excellent cycle performance, low expansion, and excellent comprehensive performance, which is beneficial to the use of the battery, and compared with other embodiments, the battery provided in embodiment 1 has better performance and good comprehensive performance. Therefore, the silicon-based negative electrode material provided in this application can effectively improve the performance of the battery and is beneficial to the use of the battery.
[0088] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be noted that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A silicon-based negative electrode material, characterized in that: It comprises a silicon-based core and a coating layer coating the silicon-based core, wherein the coating layer is made of carbon material and a fast ion conductor, and the mass content of the fast ion conductor in the coating layer gradually increases along the direction from the silicon-based core to the coating layer.
2. The silicon-based negative electrode material according to claim 1, characterized in that: Along the direction from the silicon-based core to the coating layer, the mass content of the fast ion conductor in the coating layer gradually increases from 15%-25% to 60%-70%.
3. The silicon-based negative electrode material according to claim 1, characterized in that: The thickness of the coating layer is 5nm-50nm, and the particle size of the silicon-based core is 25nm-50nm.
4. The silicon-based negative electrode material according to claim 1, characterized in that: The mass content of the silicon-based core in the silicon-based negative electrode material is 50%-70%, and the mass content of the coating layer is 30%-50%.
5. The silicon-based negative electrode material according to claim 1, characterized in that: The fast ion conductor includes at least one of zirconium oxide, aluminum oxide, thorium dioxide, hafnium dioxide, germanium dioxide, bismuth oxide, lanthanum aluminate, calcium titanate, strontium titanate, calcium fluoride, lead difluoride, stannous chloride and silver iodide.
6. The silicon-based negative electrode material according to claim 1, characterized in that: The silicon-based negative electrode material further includes a carbon layer, which covers the coating layer, and the thickness of the carbon layer is 2nm-10nm.
7. A method for preparing a silicon-based negative electrode material, characterized in that: include: A coating layer covering the silicon-based core is formed on the surface of the silicon-based core to obtain a silicon-based negative electrode material. The material of the coating layer includes a carbon material and a fast ion conductor. Along the direction from the silicon-based core to the coating layer, the mass content of the fast ion conductor in the coating layer gradually increases.
8. The preparation method according to claim 7, characterized in that: include: The silicon source is mixed with a fast ion conductor source and a carbon source and then sintered to obtain the silicon-based negative electrode material. The silicon source forms the silicon-based core, the fast ion conductor source forms the fast ion conductor, and the carbon source forms the carbon material.
9. A negative electrode, characterized in that: It comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises the silicon-based negative electrode material according to any one of claims 1 to 6, or the silicon-based negative electrode material prepared by the preparation method according to any one of claims 7 to 8.
10. A battery, characterized in that: It comprises a positive electrode and the negative electrode as claimed in claim 9.
11. An electrical device, characterized in that: Comprising the battery as claimed in claim 10.
Citation Information
Cited By
All-solid-state lithium-selenium battery composite positive electrode material as well as preparation method and application thereof
CN122436481A